Cyberbullying Prevention: Enhancing Digital Literacy at SMA 3 Pekanbaru: Pencegahan Cyberbullying: Peningkatan Literasi Digital di SMA Negeri 3 Pekanbaru - Rianita, Dian; Sihombing, Alentina; Ramadhan Arfi, Ridho; Husna, Khuriyatul; Yandra, Alexsander (Universitas Lancang Kuning, 2025)
Cyberbullying is a complex problem that requires integrated handling. The advancement of technology among teenagers can increase the cyberbullying. A team from the Faculty of Administration conducted community service at SMAN 3 Pekanbaru on the issue of cyberbullying by educating the students about the detrimental effects of cyberbullying on social development and mental health, as well as strategies for overcoming them. The methods used include lectures, discussions, questions and answers, and illustrations of the impact of cyberbullying. The results of this activity show an improvement in participants' knowledge and awareness of the dangers of cyberbullying. Evaluation of this activity can help reduce the number of cyberbullying incidents among students and foster a more positive technology use culture in schools. The evaluation revealed that the socialization program effectively enhanced students' knowledge and awareness. This enables them to actively contribute to fostering a secure school atmosphere devoid of cyber aggression. PKM also emphasized that teacher and parent involvement can reduce the number of bullying cases on social media.